2012
DOI: 10.1111/j.1442-200x.2011.03549.x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric cases of Crimean‐Congo hemorrhagic fever in Turkey

Abstract: CCHF virus infections are seen mostly in boys and school children and the adolescent age group. Tick bite is the major risk factor. Fever and hemorrhage are the most frequent presenting symptoms. Tonsillopharyngitis and rash on face or body are probably the most remarkable clinical findings in this disease. The CCHF disease course in Turkey may be mild in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 18 publications
(104 reference statements)
0
27
0
5
Order By: Relevance
“…9,10 In a study evaluating 50 children with CCHF, no fatality was observed, which is similar to our findings. 17 These results suggest that the disease course is milder among children in Turkey, but in a study from Iran, the CFR was as high as 26.5% and the mean age of the patients was 13.3 years and the youngest patient was 5 years of age. 18 In our study, the mean age was 10.6 years and the youngest patient was 1 year of age.…”
Section: Discussionmentioning
confidence: 72%
“…9,10 In a study evaluating 50 children with CCHF, no fatality was observed, which is similar to our findings. 17 These results suggest that the disease course is milder among children in Turkey, but in a study from Iran, the CFR was as high as 26.5% and the mean age of the patients was 13.3 years and the youngest patient was 5 years of age. 18 In our study, the mean age was 10.6 years and the youngest patient was 1 year of age.…”
Section: Discussionmentioning
confidence: 72%
“…Fever (100%), hemorrhagic symptoms (76%), nausea-vomiting (60%), tonsillopharyngitis (50%), malaise (50%), myalgia (46%), and maculopapular rash (24%) are the most common presenting clinical features (4). Hyponatremia or any electrolyte imbalance has not been reported before.…”
Section: Discussionmentioning
confidence: 97%
“…Hyponatremia symptoms are nausea, anorexia, emesis, malaise, lethargy, confusion, agitation, headache, seizures, muscle cramps, weakness, coma, and decreased reflexes. Most symptoms of hyponatremia are due to the decrease in extracellular osmolality (4).…”
Section: Introductionmentioning
confidence: 99%
“…CCHF was first observed in Turkey in 2002, and from 2002 to 2010, 5321 patients were reported [2]. CCHF remains a seasonal problem in the Mid-Eastern Anatolia region of Turkey to date.…”
Section: Discussionmentioning
confidence: 98%